1989
DOI: 10.1029/ja094ia09p11761
|View full text |Cite
|
Sign up to set email alerts
|

Planar magnetic structures in the solar wind

Abstract: A distinctive magnetic structure in which azimuthal and latitudinal angles of field vectors axe closely related to each other has been found in the interplanetary magnetic field data obtained by Sakigake at 0.8-1.0 AU. In this structure, termed a "planar magnetic structure" (PMS), the magnetic field vectors are nearly parallel to a fixed plane. This plane includes the spiral direction but is inclined to the ecliptic plane from 30 ø to 85 ø . The field vectors take almost all directions parallel to this plane. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 27 publications
5
106
0
Order By: Relevance
“…The draping of the IMF is also one of the primary causes creating "planar magnetic structures" (PMSs) (e.g., Nakagawa et al 1989) within ICME sheath regions (e.g., Neugebauer et al 1993). These are periods when the variations of the magnetic field occur parallel to a single plane.…”
Section: Large-scale Sheath Structuresmentioning
confidence: 99%
“…The draping of the IMF is also one of the primary causes creating "planar magnetic structures" (PMSs) (e.g., Nakagawa et al 1989) within ICME sheath regions (e.g., Neugebauer et al 1993). These are periods when the variations of the magnetic field occur parallel to a single plane.…”
Section: Large-scale Sheath Structuresmentioning
confidence: 99%
“…The draping field lines ahead of an ICME into a plane of compression may lead to the formation of a "planar magnetic structure" (PMS). Nakagawa et al (1989) first identified them, and suggested various mechanisms for their formation. In these regions, the field lines, although variable, lie in a common plane.…”
Section: Determining the Shock Normalmentioning
confidence: 99%
“…The original suggestion for the cause of PMSs was that they were signatures of the passage of the observing spacecraft through magnetic "tongues" or "islands" [Nakagawa et al, 1989]; it was suggested that these could be formed by solar reentrant loops.…”
Section: Pms Formation In the Vicinity Of The Sunmentioning
confidence: 99%